Feasibility of Pay for Performance and Transparency Interventions on the Selection and Quality of Observational Management for Patients With Low-Risk Prostate Cancer in the Community Practice - Gaylis, Franklin D; Leapman, Michael S; Ellis, Shellie D; Hu, Steven; Cooperberg, Matthew R; Loeb, Stacy; Chen, Ronald C; Cohen, Edward S; Dato, Paul E; Aynehchi, Shahrad; David, Richard; Topp, Robert; et al. (Urology practice, 2025)
Practice-level strategies to improve the use of conservative management for low-risk prostate cancer have not been rigorously evaluated. We examined the feasibility of implementation and preliminary outcomes of a pay-for-performance (P4P) and a transparency intervention at the practice level. We conducted a pilot study within a Southern California urology practice network. We developed and implemented a value-based model based on quality metrics for patients with low-risk prostate cancer (LR PCa) consisting of a financial incentive to the urology practice paid by a large commercial payer, as well as performance transparency (audit and feedback) reporting to participating providers. The primary outcome was the increase in use of conservative management (active surveillance or watchful waiting) from baseline to the intervention periods (2019-2022/23). We evaluated conservative therapy among patients for whom financial incentives were eligible as well as noneligible patients. Following the introduction of transparent physician audit and feedback and P4P intervention, adoption of conservative management (active surveillance or watchful waiting) increased from 65.5% (93/142) to 83% (125/150), respectively ( < .001). Increases in conservative management for LR PCa, post intervention, were observed in both patients for whom performance incentives were eligible (94%) as well as noneligible (82%) patients. P4P and transparent audit and feedback collaborative interventions to promote adherence to evidence-based quality measures were both feasible and associated with increased use of conservative management of patients with LR PCa. Physician audit and feedback (transparency) appears to have the strongest influence on physician adoption of conservative management.